Hopalong Cassidy. [videorecording (DVD)] - Selander, Lesley, 1900-1979; Archainbaud, George, 1890-1959; Boyd, William, 1895-1972; Clyde, Andy, 1892-1967; Brooks, Rand; Hayden, Russell, 1912-1981; Wood, Britt (Echo Bridge Home Entertainment, 2007)
Hopalong Cassidy and his trusty stallion, Topper, rode into the hearts of millions in the 1940s as the good-guy of the West. Follow Hopalong and his Bar 20 Ranch gang as they wrangle with the outlaws.